Building Up Alliances and Breaking Down the State Monopoly: The Rise of Non-Governmental Disaster Relief in China. (10th April 2018) - Peng, Lin; Wu, Fengshi
Abstract: This paper explores the emergence of a highly networked and capable non-governmental organization (NGO) community in disaster relief in China. It provides a review of the growth of non-governmental actors in the relief field since the 2000s and examines the most important platforms and networks in the field, focusing on their strategies of maintaining a broad-based partnership, developing their own capacity, and enhancing overall inter-organizational connectivity. With an in-depth look at a successful joint non-governmental relief operation in Lushan in 2013, the paper also explicates how NGOs can break the state monopoly over disaster information management, public donations and relief operations. This research finds that during crisis times, non-governmental actors carry out relief missions effectively in parallel with state agencies. The rise of non-governmental disaster relief sheds light on one of many trajectories of civil society development in China where social autonomy is earned by innovation, public support and improved capacity. 摘要: 民间自发救灾在中国最近几年蓬勃发展起来, 已经开始形成具有专业化能力的社会组织网络。本研究首先回顾了二十一世纪以来民间力量和非政府组织参与救灾的发展历程, 详细分析最具代表性的平台和网络组织, 并且重点解释民间组织是如何维持广泛的伙伴关系, 如何促进跨组织的协调和联系来推动一个全国范围的具有集体认同的民间救灾共同体的形成。本研究还以 2013 年芦山地震救灾作为案例来解释不同的民间力量是如何通过有意识的组织建设和策略创新逐渐打破政府在灾情信息、社会捐助以及救灾管理方面的垄断地位, 开辟出一个同国家救灾体系平行、保持相对独立的民间救灾体系。不需要同政府发生直接对抗和冲突, 这个联动、高效和专业的民间救灾体系已经能够在某些方面替代国家的救灾功能, 甚至已经发展出一些不同于国家的救灾机制。通过这个案例, 本研究希望能够揭示中国公民社会发展的一种可能路径; 沿着这条路径, 公民社会有可能在既不全面被政权所压制, 也不必然会同国家正面冲突的情况下依靠公众的支持、创新和自我管治能力来发展社会自主性。